Assessment of Arabic Communication Skills Textbook for Eighth Grade by Teachers in Jordanian Schools - Khalaf, Rasha Eyade; Alqadi, Haitham Mamdouh (Dirasat: Educational Sciences, 2021)
The study aims at identifying how communication skills curriculum of eighth grade is evaluated from the point of view of Arabic language teachers in Jordan. The study sample consisted of (184) male and female teachers from the first and second departments of education at Amman. The researchers developed a questionnaire consisting of (47) items distributed on five domains (form and instruction, objectives, content, activities and educational means, and procedures of evaluation). The results of the study revealed that the evaluation degree of the curriculum was high in all areas except the domain of activities and educational means which had an average evaluation level. The results showed statistically significant differences in favor of male teachers in the domain of form and instruction evaluation, while there were no statistically significant differences attributed to academic qualification or experience.